SCHOLARSHIP AND THE CRITIQUE OF TRADITION: Elliot R. Wolfson, Heidegger and Kabbalah: Hidden Gnosis and the Path of Poiēsis. Issue 4 (27th December 2020) - Novak, David
Abstract: This review essay of Wolfson's recent Heidegger and Kabbalah both praises Wolfson for departing from the historicism of his earliest writings on the kabbalistic tradition, and also critiques him for being unable to ground adequately his critique of the kabbalistic tradition's ethnocentrism. Resolving the tension in this authorial position, stretched between commitment to a particular tradition and the liberalism of much of contemporary academia, entails acknowledging the limitations of scholarship in religious ethics.